A aprendizagem integral proposta pela rede jesuíta de educação e o brincar heurístico - Veiga, Larissa Alves (Universidade do Vale do Rio dos Sinos, 2023)
This article discusses the relationship between comprehensive learning and heuristic play in very young children. The aim of this research is to analyze and describe the connection between comprehensive learning and heuristic play in Early Childhood Education, focusing on children aged 2 and 3. The methodology employed is qualitative, based on bibliographic and documentary sources following Gil (1991). Key theoretical contributions come from Ariès (1981), Goldschmied and Jackson (2006), Rousseau (1971), the National Common Curricular Base (2017), Meirelles (2016), and documents from the Jesuit Education Network, among others. Following the research, it is concluded that the historical and social construction of childhood and the child is recent and evolves over the years within society. Comprehensive learning, advocated by the Society of Jesus, aims to form global citizens in their entirety, considering all dimensions that constitute each individual. Heuristic play similarly embodies the child's intentionality to understand themselves and explore the world around them, engaging with peers, exploring social spaces, the home environment, objects that shape their world, and nature as a playful element. In early childhood education, approaches like heuristic play enable the expansion of individual experiences and repertoires for each child.
Keywords: Educação infantil; Aprendizagem integral; Brincar heurístico; Early childhood education; Comprehensive learning; Heuristic play